The impact of the Grand Paris Express on the European regions: A RHOMOLO analysis - Francesco Di Comite; Giovanni Mandras; Stylianos Sakkas (European Commission, Joint Research Centre (JRC), 2019)
This technical report illustrates a simulation performed to assess the likely economic impact of the Grand Paris Express investments on the Île-de-France and the other European Union regions, under the working assumption of a combined 1% increase in labour productivity due to better matching between skill supply and demand and a 1% increase in accessibility due to the project. Our simulations suggest an overall medium-term positive GDP impact for the EU as a whole (0.18%), for France (0.79%) and for Île-de-France (2.61%).
Keywords: C67; C68; R13; R58; 330; rhomolo; region; growth; spatial general equilibrium model; Grand Paris; investment; labour productivity; transportation cost